Isolation and Evaluation of Potential Use of Prebiotics—Utilizing Butyrate-Producing Bacteria in Nibea coibor - Zhongzhen Li; Ngoc Tuan Tran; Ming Zhang; Zhaoxi Li; Wanying Yang; Shuqi Wang; Zhong Hu; Shengkang Li (Aquaculture Nutrition)
Butyrate-producing bacteria (BPB) benefit the health of aquatic animals. This current study aimed to isolate BPB from the intestines of Nibea coibor and assess their probiotic potential. The results showed that nine isolates were obtained in vitro from the gut of N. coibor, including six Clostridium butyricum, two Proteocatella sphenisci, and one Fusobacterium varium. The representative bacteria, C. butyricum CG-3 and P. sphenisci DG-1, which produce high butyrate levels, were further studied for short-chain fatty acid (SCFA) production and antibiotic susceptibility. The effects of BPB singly (CB: basal diet + CG-3 and PS: basal diet + DG-1, at 107 CFU/g) or in combination with galactooligosaccharides (GOS) (0.5%) and inulin (0.5%) (CBIG) or D-sorbitol (0.5%) (PSGS) on the growth and health status of N. coibor were investigated. Results showed an increase in growth parameters in the CB, CBIG, and PSGS groups, except for the PS group. Alterations in intestinal microbiota (including diversity, abundance, and function) were observed in four experimental groups (CB, CBIG, PS, and PSGS groups). SCFA contents increased in treated groups; butyrate production was positively related to bacterial abundance. Compared to control, levels of complement C3, complement C4, immunoglobulin M (IgM), transforming growth factor-β (TGF-β), interleukin (IL)-10, IL-1β, and lysozyme (LZM) increased, while malondialdehyde (MDA) decreased in treated groups. Contents of IL-6 (PS and PSGS groups), tumor necrosis factor-alpha (TNF-α) (CB, PS, and PSGS groups), total antioxidant capacity (T-AOC) (CB and PS groups), total superoxide dismutase (T-SOD) (PS group), catalase (CAT) (CB and PSGS groups), and activities of amylase (PS and PSGS groups), trypsin (CB group), and lipase (CBIG group) were increased. Our results suggested the potential use of C. butyricum CG-1 or P. sphenisci DG-1 singly or in combination with prebiotics improved growth and health conditions in N. coibor.